Strategic Environmental Assessment (SEA) on The Revision of The Spatial Plan of Sorong District Year 2012-2032 - Murni, Murni; Madaul, Rahful Ahmad; Abu, Nur (Universitas Lambung Mangkurat, 2023)
This research aims to analyze the Strategic Environmental Assessment (SEA) in the revision of the Sorong Regency Regional Spatial Planning (RTRW) for 2012-2032. This research uses a qualitative descriptive method to achieve two objectives: (a) Provide a comprehensive analysis of the phenomenon being studied, and (b) be sensitive in collecting descriptive qualitative information while maintaining the unity of the research object, which means the data in the case study is studied thoroughly. The results of the research show that (a) In the Strategic Environmental Assessment (SEA) in the 2012-2032 Revision of the Regional Spatial Plan (RTRW) of Sorong Regency, it was identified that there were 8 KRP Spatial Structure Plans and 6 Spatial Patterns that had the potential to influence environmental conditions, based on analysis of the impact of sustainable development issues on spatial planning policies; (b) The results of the analysis regarding the influence of sustainable development issues on policies, plans and programs show that of the 9 KRPs analyzed, only 3 items require a study of SEA content, while the other 6 items do not require a study of SEA content. In addition, of the 6 Spatial Patterns in the KRP, all require a study of SEA content; and (c) The purpose of the alternative formulation is to agree on improvements to the KRP based on the results of the alternative formulation, supporting follow-up steps will be formulated as a result of the implementation of the KRP.